Political Reform in the General Election - Yusriadi Yusriadi; Armin Anwar; Enni Enni (Universitas Medan Area, 2020)
A country can be called upholding the values of democracy if, in that country, there is a guarantee in freedom of thought and opinion. And, of all of that, one of them was realized by the existence of elections. As a country that adheres to the principle of democracy, it is important for Indonesians to have a process for selecting people to fill certain political positions. 2019 Election becomes a new chapter for Indonesia in holding general elections, more than 187 million voters both domestically and abroad for the first time will elect simultaneously legislative and vice-presidential candidates. This study illustrates political reform in elections in Indonesia, In the 2019 Election, the competition of political parties to qualify for the House of Representatives was increasingly difficult. The parliamentary threshold that must be achieved by political parties to place their cadres in the House of Representatives rose to 4 percent in the 2019 Election. That number rose 0.5 percent compared to the 2014 legislative elections of 3.5 percent.